Uranium Transport in F-Cl-Bearing Fluids and Hydrothermal Upgrading of U-Cu Ores in IOCG Deposits - Yanlu Xing; Yuan Mei; Barbara Etschmann; Weihua Liu; Joël Brugger (Geofluids)
Uranium mineralization is commonly accompanied by enrichment of fluorite and other F-bearing minerals, leading to the hypothesis that fluoride may play a key role in the hydrothermal transport of U. In this paper, we review the thermodynamics of U(IV) and U(VI) complexing in chloride- and fluoride-bearing hydrothermal fluids and perform mineral solubility and reactive transport calculations to assess equilibrium controls on the association of F and U. Calculations of uraninite and U3O8(s) solubility in acidic F-rich (Cl : F = 100 [ppm-based]) hydrothermal fluids at 25–450°C, 600 bar, show that U(IV)-F complexes (reducing conditions) and uranyl-F complexes (oxidizing conditions) predominate at low temperature (T<~200°C), while above ~250°C, chloride complexes predominate in acidic solutions. In the case of uraninite, solubility is predicted to decrease dramatically as U(IV)Cl22+ becomes the predominant U species at T>260°C. In contrast, the solubility of U3O8(s) increases with increasing temperatures. We evaluated the potential of low-temperature fluids to upgrade U and F concentrations in magnetite-chalcopyrite ores. In our model, an oxidized (hematite-rich) granite is the primary source of F and has elevated U concentration. Hydrothermal fluids (15 wt.% NaCl equiv.) equilibrated with this granite at 200°C react with low-grade magnetite-chalcopyrite ores. The results show that extensive alteration by these oxidized fluids is an effective mechanism for forming ore-grade Cu-U mineralization, which is accompanied by the coenrichment of fluorite. Fluorite concentrations are continuously upgraded at the magnetite-hematite transformation boundary and in the hematite ores with increasing fluid : rock (F/R) ratio. Overall, the model indicates that the coenrichment of F and U in IOCG ores reflects mainly the source of the ore-forming fluids, rather than an active role of F in controlling the metal endowment of these deposits. Our calculations also show that the common geochemical features of hematite-dominated IOCG deposits can be related to a two-phase process, whereby a magnetite-hematite-rich orebody (formed via a number of processes/tectonic settings) is enriched in Cu ± U and F during a second stage (low temperature, oxidized) of hydrothermal circulation.